FARMER PERSPECTIVES ON RICE-FISH FARMING INNOVATION AND RISK IN SUNGAI REBO VILLAGE, BANYUASIN REGENCY - Dewi Safitri; Dessy Adriani; Yulian Junaidi (Jurusan Sosial Ekonomi Pertanian Fakultas Pertanian Universitas Mataram, 2026)
Rice-fish farming (Mina Padi) has been promoted as an integrated agribusiness strategy in tidal lowland areas. This study analyzed farmer characteristics, perceived innovation attributes, farming risks, and organizational experience in Sungai Rebo Village, Banyuasin Regency. A descriptive quantitative approach was applied using survey data from 100 rice farmers, analyzed through a Likert-scale index and boxplot visualization. Compatibility (mean = 3.86), trialability (3.82), and observability (3.87) cluster at higher Likert values, while relative advantage is perceived as moderate (3.69). Complexity displays the widest dispersion and the lowest mean score (3.18), indicating heterogeneous technical understanding among farmers. Perceived farming risks are dominated by economic and biological factors, particularly price fluctuation (3.94), low productivity (3.85), and pest and disease attacks (3.74). In contrast, flooding and dyke construction costs are consistently rated as very low risk (mean = 1.00). Organizational experience is generally moderate to high, with organizational status recording the highest mean (4.17), whereas information and technology utilization show greater variability (3.49 and 3.44). These findings indicate that farmers’ evaluations of rice–fish farming are primarily influenced by perceived manageability, economic uncertainty, and organizational capacity rather than environmental constraints alone.